2022
DOI: 10.3390/horticulturae8100945
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Biological Activities of Diospyros villosa (L.) De Winter Leaf and Stem-Bark Extracts

Abstract: This study aimed to evaluate the phytochemical components, antioxidant capacity, and antimicrobial effects of Diospyros villosa (L.) De Winter leaves and stem bark. The extracts were obtained using different media (methanol, chloroform, and hexane). The DPPH and FRAP methods were used to assess the antioxidant activity and the Folin–Ciocalteu method was used to determine the total phenolic contents of the crude extracts. The antimicrobial effects of the extracts against five pathogenic bacteria were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
0
1
Order By: Relevance
“…Additionally, young stem hexane extracts of R. pyrifolius contain n-hexadecanoic acid compounds in small amounts of 6.54%. This result contrasts with Adu et al (2022), who reported that n-hexadecanoic acid (11.77%) was found in the hexane leaf extract and stem extract of Diospyros villosa in high proportions.…”
Section: Gc/ms Analysis Of the Plant Extractcontrasting
confidence: 84%
“…Additionally, young stem hexane extracts of R. pyrifolius contain n-hexadecanoic acid compounds in small amounts of 6.54%. This result contrasts with Adu et al (2022), who reported that n-hexadecanoic acid (11.77%) was found in the hexane leaf extract and stem extract of Diospyros villosa in high proportions.…”
Section: Gc/ms Analysis Of the Plant Extractcontrasting
confidence: 84%